Factors That Influence Consumer Decision In Wedding Vendor Selection - Muhamad Randy Wiguna Semesta; Idqan Fahmi; Siti Jahroh (Jurnal Manajemen, 2020)
The purpose of this study is to analyze consumers' perceptions of wedding vendors to the current marketing mix of services, reference groups, and purchase decisions. Analyze the effect of the services marketing mix and reference group on the purchase decision. Formulate an effective marketing strategy for wedding vendors in influencing consumer purchasing decisions. 208 people of samples, with purposive sampling. Analytical tools use descriptive analysis, SEM-PLS, and IPA. Consumer perception of service marketing mix and purchase decision is a good category, while the reference group is in fair category. Services marketing mix has a significant positive effect on the purchasing decisions of the wedding vendor, while the reference. group has. no significant effect on the purchasing decisions of the wedding vendor.Marketing strategies that can be improved to improve purchasing decisions so that is following the priority indicators that have a high level of importance, but have a level of performance that is still below average.